Keanekaragaman Jenis Amfibi (Ordo Anura) Pada Beberapa Tipe Habitat Di Youth Camp Desa Hurun Kecamatan Padang Cermin Kabupaten Pesawaran - Yudi Safril Ariza; Bainah Sari Dewi; Arief Darmawan (Jurnal Sylva Lestari, 2014)
Amphibian is one of important ecosystem component, both ecologicaly and economically. Research about amphibian in Indonesia is still very limited. In Sumatra, one of Indonesia's largest islands, there hasn't been much attention on research about amphibians. This study aimed to compari the diversity of nocturnal amphibians (Ordo Anura) about at Youth Camp on habitat types. This study was implemented at three different types of habitat, (1) forest, (2) plantations, and (3) rivers. The data was collected by visual encounter survey using line transect method. Identification was book using identification guidebook. The data was analyzed descriptively as well as statistically to calculate species richness and shannonwiener biodiversity index and evenness index. There were 105 individuals comprising 15 species of amphibians and 5 families: Bufonidae 3 species, Megophrydae 1 species, Microhylidae 2 species, Ranidae 7 species, and Rhacophoridae 2 species. Forest habitat found 8 species, plantation habitat 5 species, and river habitat 7 species. The biodiversity index of amphibian at three habitat being categori and evenness index are forest habitat J=0,695, plantation habitat J=0,578 and river habitat J=0,477. Keywords: amphibians, diversity, Hanura, Youth Camp